Study of the Propagation Characteristics of Terahertz Waves in a Collisional and Inhomogeneous Dusty Plasma with a Ceramic Substrate and Oblique Angle of Incidence - Qingwen Rao; Guanjun Xu; Pengfei Wang; Zhengqi Zheng (International Journal of Antennas and Propagation)
In this paper, the propagation properties of a terahertz (THz) wave in a collisional and inhomogeneous dusty plasma with a ceramic substrate and oblique angle of incidence are studied using the scattering matrix method. The influence of the various corresponding parameters, such as the frequency of the THz wave, angle of incidence, electron density, radius and density of the dust particles, and the collision frequency, on the absorbance and transmittance is calculated. The results of the simulation indicate that an increase in the wave frequency increases the transmittance and decreases the absorbance. Moreover, the absorbance of a THz wave in a dusty plasma with a ceramic substrate increases with an increase in the incident angle, maximum electron density, coefficient of steepness, density and radius of the dust particles, and collision frequency. These results provide an important theoretical basis for the problem of communication blackout between ground and spacecraft.